PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR SISTEM KOORDINASI PADA SISWA DI SMA NEGERI 2 BANTAENG - Melli Fitriani (Jurnal Biotek, 2017)
The study aims at examining the influence of problem based learning models to student’s motivation. The study was a quasy experiment. The population of the study was the entire class of grade XI IPA of second semester at SMAN 2 in Bantaeng district of academic year 2016/2017. Data were taken by employing random sampling. Data were obtained by employing of Quesioner for student Motivation. Data were analyzed by using descriptive and inferential analyzes. The result of the study reveals that Problem Based Learning Model was’nt influenced to student motivation significansi 0,371 > 0,05,